2017
DOI: 10.1111/scs.12546
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with medication administration errors and why nurses fail to report them

Abstract: Medication errors by nurses are related to medication packaging, poor communication, unclear medication orders, workload and staff rotation. To prevent medication errors, teamwork must be improved. All healthcare settings should emphasise awareness of the culture of safety, provide support and guidance to nurses and improve communication skills. We also recommend the use of integrated health informatics, including computerised drug administration systems. The limitations of this study include the potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 17 publications
6
92
0
12
Order By: Relevance
“…Studies previously done elsewhere, have similarly found erroneous prescriptions among the most contributing factors to MAEs, where nurses experience drug errors occurring when a physician prescribes a wrong dose [38,45] as well as when physicians allot insufficient time to discuss suggested care with nurses. Similar to the present study; Hammoudi, Ismaile & Abu-Yahya (2017) recently found low agreement rates given in response to questions on transcribing documentation factors in their study [41], indicating the low perception or consideration by nurses of the scale items as a possible cause of MAEs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Studies previously done elsewhere, have similarly found erroneous prescriptions among the most contributing factors to MAEs, where nurses experience drug errors occurring when a physician prescribes a wrong dose [38,45] as well as when physicians allot insufficient time to discuss suggested care with nurses. Similar to the present study; Hammoudi, Ismaile & Abu-Yahya (2017) recently found low agreement rates given in response to questions on transcribing documentation factors in their study [41], indicating the low perception or consideration by nurses of the scale items as a possible cause of MAEs.…”
Section: Discussionsupporting
confidence: 87%
“…A further comparison of the medication packaging subscale mean scores between the medical and surgical units revealed statistically significant mean differences between the two units (t=4.160, p=0.044). Several studies [11,26,41] intimate that once a medication has been unpackaged, from its original packet it can easily be mistaken with other look alike medications and therefore it should be immediately dispensed to the patient to avoid MAEs.…”
Section: Discussionmentioning
confidence: 99%
“…They also have to mediate between doctor and patient and create a communication bridge so that optimum results of treatment are achieved [15]. Peplau's theory [17,18], is one of the greatest works in the fi eld of nursing relationships and interpersonal communications and it emphasize on reciprocity between nurses and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Medication error could be associated with numerous factors, such as poor coordination of care, cost-related barriers, multi-morbidity, increasing days of hospitalization, childhood and older age, lack of training, inadequate knowledge, inadequate perception of risks, overworked healthcare professionals, distractions, lack of standardized protocols, and insu cient resources. Medication packaging problem, poor nurse-physician communication, and problem in recruiting competent professional were also the suggested reasons [15].…”
Section: Introductionmentioning
confidence: 99%